![](https://rs.olm.vn/images/avt/0.png?1311)
Hãy nhập câu hỏi của bạn vào đây, nếu là tài khoản VIP, bạn sẽ được ưu tiên trả lời.
![](https://rs.olm.vn/images/avt/0.png?1311)
![](https://rs.olm.vn/images/avt/0.png?1311)
![](https://rs.olm.vn/images/avt/0.png?1311)
![](https://rs.olm.vn/images/avt/0.png?1311)
x2-x-12=x2+3x-4x-12=(x2+3x)-(4x+12)=x(x+3)-4(x+3)=(x+3)(x-4)
![](https://rs.olm.vn/images/avt/0.png?1311)
\(x^2-x-12\)
\(=x^2-x-12\)
\(=\left(x-4\right)\left(x+3\right)\)
![](https://rs.olm.vn/images/avt/0.png?1311)
3. ( 22 + 1 ).( 24 + 1 ).( 28 + 1 )......( 264 + 1 ) + 1
= ( 22 - 1 ).( 22 + 1 ).( 24 + 1 ).( 28 + 1 )....( 264 + 1 ) + 1
= ( 24 - 1 ).( 24 + 1 ).( 28 + 1 )......( 264 + 1 ) + 1
= ( 28 + 1 ).....( 264 + 1 ) + 1
= ( 264 - 1 ).( 264 + 1 ) + 1
= 2128 - 1 + 1
= 2128
8.( 32 + 1 ).( 34 + 1 ).( 38 + 1 )....( 3128 + 1 ) + 1
= ( 32 - 1 ).( 32 + 1 ).( 34 + 1 ).( 38 + 1 )....( 3128 + 1 ) + 1
= ( 34 - 1 ).( 34 + 1 ).( 38 + 1 )....( 3128 + 1 ) + 1
= ( 38 - 1 ).( 38 + 1 )....( 3128 + 1 ) + 1
= ( 316 - 1 )......( 3128 + 1 ) + 1
= ( 3128 - 1 ).( 3128 + 1 ) + 1
= 3256 - 1 + 1
= 3256
![](https://rs.olm.vn/images/avt/0.png?1311)
\(S=4\cdot\left(3^2+1\right)\left(3^4+1\right)\left(3^8+1\right)\cdot...\cdot\left(3^{64}+1\right)\)
\(\left(3^2-1\right)S=4\cdot\left(3^2-1\right)\left(3^2+1\right)\left(3^4+1\right)\left(3^8+1\right)\cdot...\cdot\left(3^{64}+1\right)\)
\(8S=4\cdot\left(3^4-1\right)\left(3^4+1\right)\left(3^8+1\right)\cdot...\cdot\left(3^{64}+1\right)\)
\(2S=\left(3^8-1\right)\left(3^8+1\right)\cdot...\cdot\left(3^{64}+1\right)\)
...
\(2S=3^{128}-1\)
Vậy S < 3128 - 1
![](https://rs.olm.vn/images/avt/0.png?1311)
Ta có A = (32 + 1)(34 + 1)(38 + 1)(316 + 1)(332 + 1)(364 + 1)
=> 8A = 8(32 + 1)(34 + 1)(38 + 1)(316 + 1)(332 + 1)(364 + 1)
=> 8A = (32 - 1)(32 + 1)(34 + 1)(38 + 1)(316 + 1)(332 + 1)(364 + 1)
=> 8A = (34 - 1)(34 + 1)(38 + 1)(316 + 1)(332 + 1)(364 + 1)
=> 8A = (38 - 1)(38 + 1)(316 + 1)(332 + 1)(364 + 1)
=> 8A = (316 - 1)(316 + 1)(332 + 1)(364 + 1)
=> 8A = (332 - 1)(332 + 1)(364 + 1)
=> 8A = (364 - 1)(364 + 1)
=> 8A = 3128 - 1 (1)
Đặt B = 3126
=> 8B = 3126 . 8 = 3126.(32 - 1) = 3128 - 3126 (2)
Từ (1)(2) => 8A > 8B
=> A > B
![](https://rs.olm.vn/images/avt/0.png?1311)
A=4(32+1)(34+1)(38+1)...(364+1)
=>2A=8(32+1)(34+1)(38+1)....(364+1)
=(32-1)(32+1)(34+1)(38+1).....(364+1)
=(34-1)(34+1)(38+1)....(364+1)
=(38-1)(38+1).....(364+1)
tương tự như thế ta được
2A=3128-1
=>A\(\frac{3^{128}-1}{2}\)
=>B>A
Đặt A = ( 3 + 1 )( 32 + 1 )...( 364 + 1 ) + 1
=> 2A = 2( 3 + 1 )( 32 + 1 )...( 364 + 1 ) + 2
= ( 3 - 1 )( 3 + 1 )( 32 + 1 )...( 364 + 1 ) + 2
= ( 32 - 1 )( 32 + 1 )...( 364 + 1 ) + 2
= ( 364 - 1 )( 364 + 1 ) + 2
= 3128 - 1 + 2 = 3128 + 1
=> A = ( 3128 + 1 )/2